3D Study Of Magnetic Fields In NGC 6946. Issue Volume 10:Issue S309(2014) (9th February 2015) - Williams, Anna; Heald, George; Wilcots, Eric; Zweibel, Ellen
Abstract: Recent advancements in both radio observatories and computing have opened a new regime of 3D observations. Not only do these instruments measure emission lines and radio continuum over much larger bandpasses, but they also simultaneously observe the polarized emission over the same large bandpasses with increased sensitivity. This "polarization spectrum" can be used to recover information about the 3D structure of magnetic fields in the universe. Our combined 3-20~cm observations of NGC 6946 taken with the Westerbork Synthesis Radio Telescope provide highly sensitive diagnostics of the internal depolarization across the galaxy. We use model fitting to determine likely mechanisms for depolarization in different regions of the galaxy, and glean information about the coherent and turbulent magnetic fields in NGC 6946. We produce Faraday dispersion maps that illustrate how we can probe different depths into the galaxy at different wavelengths and display new features of the line of sight magnetic field. This work is just a sample of the new 3D studies that are possible with upgraded and new radio instruments like the VLA, ATCA, and SKA.